A Preliminary Study on the Small Population Paradigm and Nesting Biology of Rose-Ringed Parakeets (Psittacula Krameri) in Gujar Khan, Pakistan - Muhammad Bilal; Muhammad Huzaifa Zahid; Khalid Mahmood; Abdullah Ibrahim; Ali Hasnain Mosvi (Journal of Bioresource Management, 2020)
Rose-ringed parakeet (P. krameri) is commonly found native psittacid in Pakistan. It is most popular companion bird in Pakistan. It is an unprotected species as per The Punjab Wildlife Act, 1974. The objectives of the present study were to study its population paradigm and basic nesting biology in the Gujar Khan, Punjab, Pakistan. Previously, no studies were carried out to assess its live and vacant nest cavities, nesting site, nest height, cavity position on substrate, and potential roosts in the area. Moreover, this study also assesses the potential threats and factors in this area and conservation of the parakeet. Results show that in the study area (36.77%) active and (63.22%) inactive nests were found. A total of 10 tree species were utilized to make nests. It was found Ficus bengalensis, Syzygium cumini, Morus alba, Melia azedarach and Broussonetia papyrifera as the most used tree species for nesting due to more frequencies and old ages. Parakeets make nest at 3-11 m height. The preferred nest height (42.48%) was in the range of 7-9 m, while (5.88%) least at 3-5 m height. For safety reasons they made more nests (45.09%) on the tree trunk followed by terminal (31.37%) and at fork (23.52%). Due to smaller thriving population we found only (mean=7±4) parakeets during roost counting. Severe cutting of trees, destruction of its habitat and poaching for selling in the bird market are the main causes of its population decline. Government must change its status from unprotected to protected species and should ban its dealing for pet.